2017
DOI: 10.18805/lr-369
|View full text |Cite
|
Sign up to set email alerts
|

Diversity for vitamin and amino acid content in grass pea (Lathyrus sativus L.)

Abstract: This study was conducted to determine vitamin A, B, C, -carotene and amino acid profile in 18 genotypes and four grass pea (Lathyrus sativus L.) varieties which have low -ODAP. Present results indicated that retinol, -carotene, thiamine, riboflavin, niacin, pantothene, pyridoxine, folic acid and ascorbic acid ranged from 25.6 to 44.1 µg/kg; 240.8 to 410.1 µg/ kg, 3.74 to 5.44; 1.86 to 2.76; 12.37 to 20.25; 14.43 to 22.41; 4.92 to 6.62; 4.04 to 6.77 and 33.4 to 58.2 mg/kg, respectively in seeds. In addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
(32 reference statements)
1
19
0
1
Order By: Relevance
“…A-tocopherol content of O. was found between 22.2±2.64 µg/g and 1.8±0.4 µg/g while K1 content of O. was found between 1.6±0.1 µg/g and 10.2±0.97 µg/g (except for O. caput-galli and O. galegifolia which don't have K1 content) in present study. Arslan (2017) indicated that legumes include K vitamin together with vitamin B1, B2, B6, vitamin C, vitamin E. Furthermore, it was found that studied O. species have high D3 content (66.7±1.2-36.7±1.1 µg/g) in this study. Sahin et al (2009) found that Lathyrus taxa, the other genus of legumes, have high vitamin D3.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…A-tocopherol content of O. was found between 22.2±2.64 µg/g and 1.8±0.4 µg/g while K1 content of O. was found between 1.6±0.1 µg/g and 10.2±0.97 µg/g (except for O. caput-galli and O. galegifolia which don't have K1 content) in present study. Arslan (2017) indicated that legumes include K vitamin together with vitamin B1, B2, B6, vitamin C, vitamin E. Furthermore, it was found that studied O. species have high D3 content (66.7±1.2-36.7±1.1 µg/g) in this study. Sahin et al (2009) found that Lathyrus taxa, the other genus of legumes, have high vitamin D3.…”
Section: Discussionsupporting
confidence: 52%
“…Legumes are consumed high levels especially Asia, Africa and South America (Frias et al 2005) and studies showed that legumes have complex carbohyrates, vitamins, fibers, polyphenols (Oboh 2006, Amarowicz andPegg 2008). These bioactive compounds play significant role many diseases such as cancer, diabetes (Frias et al 2005, Arslan, 2017. Lipide-soluble phytonutrients such as carotenoids and tocopherols have been reported to inhibit the risk of cardiovascular, cancer, eye patologies and diabetes (Monge-Rajos and Campos 2011, Nadeau et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Grass pea seeds, however, lack sulfur-rich amino acids (methionine and cysteine) as well as tryptophan. They also contain antinutrients such as phytate, tannin, and trypsin inhibitors that have adverse effects on protein digestibility and mineral bioavailability in foods derived from grass peas (Urga et al, 2005;Arslan 2017). The major limitation for its consumption, however, is the presence of the non-proteinogenic amino acid, β-N-oxalyl-L-α,β-diaminopropionic acid (β-ODAP), a toxic compound resulting in neurolathyrism (Tamburino et al, 2012;Mondal and Puteh, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The protein content of legume seeds fall within the range of 21-25%. Legume seeds are rich in lysine and poorer in sulfur-containing amino acids when in comparison to cereals (Aniszewski et al, 2013;Arslan 2017). In the study, the mean protein content of Lathyrus taxa was 26.15% (Table 5).…”
Section: Resultsmentioning
confidence: 63%